Debate ethics education in the Quran: an examination of tafsir al-Misbah - Suherman, Eman; Sunanto , Sunanto; Muttaqien, Ghazi Abdullah; Sari, Dewi Fatimah Putri Arum (Universitas Ahmad Dahlan, 2025)
Differences in thought and opinion frequently arise in social interactions, often leading to debates. This study aims to explore how Al-Misbah interprets debate ethics in the Qur'an, emphasizing the importance of understanding ethical argumentation without causing division. Using a qualitative methodology based on library research, this study examines M. Quraish Shihab’s interpretation of Al-Misbah as reflected in several Qur’anic verses, including QS. Al-Kahf 18:54, QS. An-Nahl 16:125, QS. Ghafir 40:5, QS. Al-Hajj 22:8, and QS. Al-Ankabut 29:46. The findings indicate that teaching proper debate ethics according to the Qur'an involves revisiting these interpretations, which highlight the need for self-control (not being easily provoked by emotion), logical reasoning, and polite rhetoric free from violence or insults. Debate should be grounded in knowledge, presenting correct arguments with confidence and aiming to persuade opponents through clear and respectful communication.